PCR and DNA-probe hybridization to assess the efficacy of therapeutic and prophylactic isometamidium treatment in Trypanosoma spp. - infected dairy cattle in peri-urban Kampala, Uganda - Clausen, Peter-Henning; Schares, G.; Patzelt, R.J.; Poetzsch, C.J.; Scheer, A.; Kakaire, D.; Olila, D.; Peregrine, A.S.; McDermott, John J.; Mehlitz, D. (OAU/STRC, 2001)
In a cross-sectional study carried out in June 1994, 486 cattle from 50 randomly selected dairy farms in the vicinity of Kampala, Uganda, were examined for trypanosome infections. The trypanosome prevalence (either positive with the haematocrit centrifugation technique [HCT] and/or the mini-anion-exchange centrifugation technique [m AECT] was 18.9 %. Of these infections, 78.2 % were judged to be Trypamosoma brucei, 10.9 T vivax and 10.9 % mixed (T brucei/T vrvax). PCR gave positive results in 34.8 % of the blood samples tested, with 76.2 % positive for T brucei, 20.6 % positive for T vivax and 3.2 % positive for mixed CT. brucei 1T vrvax) infections. Using primers specific for Savannah-type T congolense, no specific products could be amplified. When the PCR-generated products were hybridized with species-specific DNA probes, the overall detection rate increased further to 43.1 %. All cattle were treated with a prophylactic dose of isometamidium chloride (I mg1kg body weight) and thereafter monitored on a monthly basis for the presence of parasitaemia and trypanosome DNA. The trypanosome prevalence (HCT and m AECT) declined, being 0.4 %, 0.7 % and 3.2 % at one, two and three months after treatment, respectively. The parasitological results were confirmed by PCR and there were neither PCR products nor hybridization signals that could be detected when testing aparasitaemic blood samples collected from cattle at the first and second month after prophylactic treatment. Parasitaemic samples collected after treatment were DNA-positive. The parasitological and DNA-based findings of this study, and additional results from in vivo and in vitro drug sensitivity studies on trypanosome field isolates collected from the study area, confirm the presence of a high level of isometamidium sensitivity amongst the trypanosome populations present in Mukono County in 1994.